A Lean Warehousing Approach to Improve OTIF in a Peruvian HVAC Distribution SME - Lezama-Colantes, Franco A.; Rojas-Núñez, Sabel S.; Chavez-Ugaz, Rafael; Leon-Chavarri, Claudia C. (LACCEI, 2025)
Heating, Ventilation, and Air Conditioning (HVAC) systems are essential for ensuring both the habitability of buildings and regulatory compliance within the construction industry in Peru. These parameters are crucial to guarantee the efficient removal of indoor pollutants and the proper intake of outdoor air, directly impacting the health, comfort, and safety of occupants. In this context, efficient management of HVAC equipment becomes critical. This paper presents a case study of a Peruvian SME specializing in ventilation systems, which faces operational challenges in its warehouse—such as obstructed aisles, disorganized storage, equipment damage from poor handling, and untracked product loans. All of which contribute to a low OTIF performance compared to industry standards. To validate the model impact, the real and improved warehouse processes were simulated using Flexsim, as software with specialized tools for simulating operator routes during the picking process, and Arena software to simulate the results obtained from the tools used in combination. Results indicate a 10% increase in OTIF performance and reductions in 5.09 minutes on picking times and space obstructions. These findings highlight how tailored Lean interventions, supported by discrete-event simulation, can strengthen performance and traceability in HVAC distribution SMEs, offering practical guidance for similar contexts in emerging economies.